Dynamism and changes in the Abia family structure and conjugal relationship: The Influence of the Nigerian Civil War (2023)
The family, as the most basic social institution, serves as the bedrock of any society. Family structures worldwide have undergone various changes in their forms, nature, and functioning, including Abia state, Nigeria. The Nigeria Civil war is one of the symbolic events attributable to changes in the Abia family structure. Changes in the family structure could influence conjugal relation¬ships. The study explored the dynamism and changes in the family structure and conjugal relationships at different eras of the family life cycle in Abia soci¬ety. A qualitative research method was used in this study. Twenty-two partici¬pants (4 life history and 18 in-depth interview participants) were recruited in this study with purposive sampling techniques. Using an archival checklist, life histories, and an in-depth guide, information was elicited on family structure and conjugal relationships. The study was subjected to thematic analysis. The findings revealed dynamism and changes in family structure, with polygyny being most prevalent prior to the civil war, the emergence of step-parent and single-parent families during the civil war, and monogamy being most prevalent, with increasing single-parent and step-parent families contemporaneously. The conjugal relationship shifted from having concubines (acceptable and practised covertly) to having side chicks (been practised covertly). The Nigerian civil war had an impact on the observed dynamics in family structure during the civil war and immediate post-civil war. Other factors such as religion, education, civilization, and migration, among others, influenced the contemporary Abia family structure. Understanding family structure dynamics could be useful in solving issues regarding family and conjugal trajectories.